National Health Interview Surveys, 1986-1994: Multiple Cause of Death, Dates of Death, 1986-1995 ([Verlag nicht ermittelbar], 1997)
This data collection supplies date and cause of death data for sample persons included in the National Health Interview Surveys (NHIS) for the years 1986 through 1994. Beginning with survey year 1986, linkage information was collected on NHIS respondents aged 18 and older to allow for matching with other data systems such as the National Death Index (NDI). The Multiple Cause of Death (MCD) data files contain information on those persons with scores high enough to be considered deceased or scores high enough that they may be included in an analysis as deceased. The Ineligible Cases data files contain person IDs of those NHIS participants under the age of 18 as well as those with insufficient information to permit linkage with the NDI. These cases should be excluded from the NHIS survey data files prior to analysis. Linkage of the NHIS respondents with the NDI provides a longitudinal component to the NHIS that allows for the ascertainment of vital status. The addition of vital status permits the use of NHIS data to estimate survival, mortality, and life expectancy while using the richness of the NHIS questionnaires, both core and supplements, as covariates. These data files must be used in conjunction with the basic NHIS data files (1986 [ICPSR 8976], 1987 [ICPSR 9195], 1988 [ICPSR 9412], 1989 [ICPSR 9583], 1990 [ICPSR 9839], 1991 [ICPSR 6049], 1992 [ICPSR 6343], 1993 [ICPSR 6534], 1994 [ICPSR 6724]). Variables included in the MCD files cover year of interview, quarter, household number, person number, month and year of death, vital status, and causes of death. The Ineligible Cases files contain a person ID that matches columns 3-16 on the NHIS public use data files.